2014
DOI: 10.1088/0031-8949/2014/t160/014023
|View full text |Cite
|
Sign up to set email alerts
|

Kicked nonlinear quantum scissors and entanglement generation

Abstract: We consider a nonlinear coupler with two Kerr-like oscillators mutually coupled by continuous linear interaction and excited by a series of ultra-short external pulses. We show that the system behaves as nonlinear quantum scissors. It evolves such a way that it can be treated as qubit-qubit system. We derive analytic formulas for the probabilities of the states involved in the system's evolution and show that they differ from those already discussed in the literature and corresponding to the continuously excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In the review paper [53] devoted to the formation of truncated quantum states in various nonlinear systems, we have shown that when coupled anharmonic oscillators are excited by ultra-short pulses, the system's evolution can be restricted to a few states only. In [79], when only one of the coupled oscillators was externally driven, we have shown that despite the continual excitations by ultra-short pulses, only four resonant states are populated and in fact, such system behaves as NQS. In consequence, the probability amplitudes corresponding to the populated states |0 |0 , |0 |1 , |1 |0 and |1 |1 show oscillatory behavior with characteristic frequencies describing their evolution [79].…”
Section: Entanglement Generation In the System With Single-mode Excitmentioning
confidence: 93%
See 3 more Smart Citations
“…In the review paper [53] devoted to the formation of truncated quantum states in various nonlinear systems, we have shown that when coupled anharmonic oscillators are excited by ultra-short pulses, the system's evolution can be restricted to a few states only. In [79], when only one of the coupled oscillators was externally driven, we have shown that despite the continual excitations by ultra-short pulses, only four resonant states are populated and in fact, such system behaves as NQS. In consequence, the probability amplitudes corresponding to the populated states |0 |0 , |0 |1 , |1 |0 and |1 |1 show oscillatory behavior with characteristic frequencies describing their evolution [79].…”
Section: Entanglement Generation In the System With Single-mode Excitmentioning
confidence: 93%
“…In [79], when only one of the coupled oscillators was externally driven, we have shown that despite the continual excitations by ultra-short pulses, only four resonant states are populated and in fact, such system behaves as NQS. In consequence, the probability amplitudes corresponding to the populated states |0 |0 , |0 |1 , |1 |0 and |1 |1 show oscillatory behavior with characteristic frequencies describing their evolution [79].…”
Section: Entanglement Generation In the System With Single-mode Excitmentioning
confidence: 93%
See 2 more Smart Citations
“…After "truncation" of the wave function describing the system, the coupler can be treated as two-qubit and treated as a Bell-like state generator that can create maximally entangled states even if the system exhibits its energy dissipating nature [5]. The system behaves similar to nonlinear quantum scissors and maximally entangled Bell states can be generated with high efficiency [6]. * E-mail: khoa_dqspqt@yahoo.com…”
mentioning
confidence: 99%